Dynamic simulation of induced voltages in high voltage cable sheaths: Steady state approach. (February 2019) - Santos, Matilde; Calafat, Miguel Angel
Highlights: New high voltage underground cables modeling approach including induced effects. Calculation of induced voltages and currents due to nearby cables and sheaths. Different types of sheaths connections and various short-circuit configurations. Simulation tool that allows the automatic generation of multiple coupling circuits. Validated by expected theoretical data and compared to ATP simulator. Abstract: This paper presents a novel approach to the modeling of high voltage underground cables. Its main contribution is that it considers induced effects. Indeed, it incorporates the estimate of induced voltages and currents in cable sheaths in steady state due to the nearby cables and sheaths, for different types of sheaths connections and for various single-phase short-circuit configurations and three-phase short-circuits. Furthermore, it allows multiple circuits to be coupled automatically in a simple way. An intuitive and friendly simulation tool has been implemented that allows the automatic generation of multiple coupling circuits and to calculate all these induced effects caused by the connection of the sheaths and the distance between cables. It has been validated by comparing it with the expected theoretical data and to other simulators with satisfactory results.